PENGARUH BUSINESS STRATEGY DAN BUSINESS RISK TERHADAP GOING CONCERN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2014 - Sefira Yovalia; Wibowo . (Lembaga Penelitian Universitas Trisakti, 2016)
he purpose of this study was to determine the effect of business strategy and business risk of the company's going concern in manufacturing companies in BEI 2010-2014. Going Concern is defined as the continuity of an entities. Business Strategy is divided into two, cost leadership strategy and differentiation strategy. The research data obtained from the annual financial statements and the company on the Exchange website Indonsia. The samples used were 144 companies manufacturing sector listed on the Stock Exchange in 2010-2014. The sampling technique used was purposive sampling. This study uses logistic regression analysis. The analytical tools used to test the hypothesis is SPSS 22. The results showed that the cost leadership strategy, differentiation strategy and business risk does not affect the going concern. However, cost leadership strategy, differentiation strategy and business risk simultanelously can affect the going concern.